APLIKASI ANJURAN PEMUPUKAN TANAMAN KOPI BERBASIS UJI TANAH DI DESA BONGANCINA KABUPATEN BULELENG - I M. Adnyana (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2011)
Survey and analysis for soil characteristics was done at land estate of Bongancina village, Buleleng regency. It aimed to give fertilization recommendation of coffee plants for increasing sustainable productivity. Soil samples were taken from top soil (0-30 cm), selected on composite sampling. Soil characteristics analysis are: soil pH, soil conductivity, organic matter, total-nitrogen, phosphorous and potassium contents. The limiting factors of coffee plants productivity were soil organic matter, nitrogen, and phosphorous. In order to manage the land estate productivity at Bongancina village, Buleleng regency, the soil fertility could be improved with integrated fertilization recommendation by combined inorganic fertilizers (Urea and SP-36) and organic fertilizers (manure and straw) with suitable dosage.